The effects of rheum officinale on the progression of feline chronic kidney disease. - Hanzlicek, Andrew S. (Kansas State University, 2011)
Chronic kidney disease (CKD) is a common cause of morbidity and mortality in cats. The purpose of this study was to investigate the effects of Chinese rhubarb (Rheum officinale) supplementation on the progression of feline CKD. Cats with stable IRIS stage II or III CKD and without certain comorbidities were included in the study. Cats were randomly divided into 3 treatment groups and administered Chinese rhubarb extract (Group 1, Rubenal®, Vetoquinol, Forth Worth, TX; 75 mg tablet by mouth every 12 h), benazepril as a positive control (Group 2, 0.5 mg/kg by mouth every 24 h), or both (Group 3). Cats were fed a commercial renal specific diet and enteric phosphate binder as appropriate. Body weight, laboratory data, and blood pressure were recorded every 3 months. Variables between groups at enrollment and within groups over visits were compared with ANOVA and repeated measures ANOVA, respectively. A treatment by visit interaction term was included in all repeated measures models. Significance was set at p ≤ 0.05. Except for body weight there was no significant differences between treatment groups at enrollment. There was no significant change in body weight, hematocrit (Hct), UPC, serum creatinine, or systemic blood pressure over time as compared to baseline within any group. There was no significant difference between groups over time in regards to change in body weight, Hct, UPC, serum creatinine, or systemic blood pressure. The treatment by time interaction was non-significant in all models. Based on easily measured clinical parameters, this study failed to detect a significant difference in cats administered a Chinese rhubarb supplement, benazepril, or both.
Keywords: Chronic kidney disease; Feline; Rheum officinale; Rhubarb; Veterinary Medicine (0778)